2004
DOI: 10.1029/2004gl020768
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters of the Bhuj earthquake, India of January 26, 2001 from height and gravity changes

Abstract: [1] Height and gravity measurements observed along a profile across the epicentral area before and after the January 26, 2001, M w 7.6 Bhuj earthquake show a maximum uplift of 1.57 ± 0.5 m and a corresponding gravity change of À393 ± 18 mGal. A best-fit, singledislocation model inverted from the height-changes using non-linear optimization methods indicates that the high-slip rupture was well contained in the aftershock zone and likely did not break to depths shallower than $10 km. Source parameters arrived in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…However they assumed a constant oblique rake of 77° over the entire fault plane and did not explore whether this secondary patch could have had a different rake. While attempting to constrain shallow slip with leveling data, Chandrasekhar et al [2004] found that strike‐slip motion dominated on a shallow fault for a model composed of 2 planar dislocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However they assumed a constant oblique rake of 77° over the entire fault plane and did not explore whether this secondary patch could have had a different rake. While attempting to constrain shallow slip with leveling data, Chandrasekhar et al [2004] found that strike‐slip motion dominated on a shallow fault for a model composed of 2 planar dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the event's remote location, no strong motion and minimal geodetic data are available within the epicentral region. The only useful geodetic data in the region are from a triangulation network last surveyed in the 19th century [ Chandrasekhar et al , 2004] and scattered GPS observations [ Jade et al , 2002]. To supplement the geodetic data, Gahalaut and Bürgmann [2004] examined satellite images to infer surface deformation from the change in the distribution of surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists working on the Bhuj event therefore struggled to constrain the parameters of the fault rupture models of the earthquake. Existing geodetic observations include sparsely distributed leveling and gravity data [ Chandrasekhar et al ., ; Wallace et al ., ], flooding pattern variations observed in optical satellite images [ Gahalaut and Bürgmann , ], isolated ERS interferogram patches [ Schmidt and Bürgmann , ], and image offsets from optical images [ Copley et al ., ]. These geodetic observations, however, failed to provide information about the near‐field deformation of the earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Even if space geodetic techniques (GPS, SAR) are more and more used for seismic, volcanic, and tectonic studies, changes in levelling data between surveys are still very useful for the investigation of seismic and volcanic sources and post‐seismic and tectonic processes (e.g. Iio et al 2002; Chandrasekhar et al 2004; Amoruso et al 2005; Battaglia et al 2006).…”
Section: Introductionmentioning
confidence: 99%